2018
DOI: 10.1021/acsami.8b20169
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Bioreactors Based on Nanoparticle-Coated Liquid Marbles for in Situ Observation of Suspending Embryonic Body Formation and Differentiation

Abstract: Transparent liquid marbles coated with hydrophobic silica nanoparticles were used as micro-bioreactors for embryonic stem cell (ESC) culturing. The high transparency of silica liquid marbles enables real-time and in situ monitoring of embryonic body (EB) formation and differentiation. The experimental result shows that ESCs can aggregate with each other close to the bottom of the liquid marble and form EBs, while remaining suspended in the culture media. The differentiation of the suspending EBs into contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…In a recent publication, the researchers suggested that the liquid marble-based 3D stem cell culture showed its potential applications in embryonic body formation and differentiation. [46] The viability of cells growing inside the LMs was determined using the 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay. As shown in Figure 7e, the optical density (O.D.)…”
Section: D Culture Of Stem Cell Spheroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication, the researchers suggested that the liquid marble-based 3D stem cell culture showed its potential applications in embryonic body formation and differentiation. [46] The viability of cells growing inside the LMs was determined using the 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay. As shown in Figure 7e, the optical density (O.D.)…”
Section: D Culture Of Stem Cell Spheroidsmentioning
confidence: 99%
“…The 3D SCSs that self‐assembled at a density of 10 6 cells mL −1 was tightly packed with ≈5000 cells in each spheroid, creating an “in vivo‐like” micro‐bioenvironment for organoid development that better preserved the stem cell phenotype and its innate properties. In a recent publication, the researchers suggested that the liquid marble–based 3D stem cell culture showed its potential applications in embryonic body formation and differentiation …”
Section: D Culture Of Stem Cell Spheroidsmentioning
confidence: 99%
“…The capability of introducing reagents and withdrawing products is crucial for liquid marbles to operate effectively as microreactors. Previous studies have reported the use of micropipettes to add and extract interior liquids without damaging liquid marbles [43][44][45][46]. However, this method requires the micropipette tips to penetrate the coating shell of liquid marbles, making the interior liquids susceptible to contamination.…”
Section: Manipulation For Opening and Closing The Liquid Marblesmentioning
confidence: 99%
“…The embryoid bodies differentiated into contractile cardiomyocytes, which can be used in cell replacement therapy. Lin et al utilised transparent liquid marbles covered with silica nanoparticles for the growth of embryoid bodies from Oct4B2-ESC and their differentiation into cardiomyocytes without transferring the embryoid bodies into another culture platform (Figure 9b) [45]. The transparency of liquid marbles allows for continuous and real-time monitoring of the formation of embryoid bodies and, eventually, the differentiation into contractile cardiac cells.…”
Section: Microbioreactors For Cell Culture and Treatmentmentioning
confidence: 99%
“…[1] However, the main industrial technologies used for urea granulation, including a prilling tower and fluidized bed granulation, have difficulty adhering to such limits owing to the insuperable dust generation according to the granulation principle, and use of an expensive and energy this range, the outer hydrophobic particle layer prevents the destruction or coalescence of liquid marbles, protecting the internal droplets from becoming independent entities. [9] Owing to their special properties, liquid marbles have been employed in various interesting applications, including those in microreactors, [10] capsule preparing, [11] microbial culture media, [12] microfluid delivery, [13] electrical sensor, [14] and magnetic sensors. [15] The merits of liquid marbles are exactly in line with the required demands of the DLUG process for continuous operation.…”
Section: Introductionmentioning
confidence: 99%